Isomeric Dithienophosphepines: The Impact of Ring Fusion on Electronic and Structural Properties - Padberg, Kevin; Ascherl, Johannes D. R.; Hampel, Frank; Kivala, Milan (Chemistry - A European Journal, 2020)
The synthesis and extensive experimental (X-ray crystallography, UV/Vis spectroscopy, cyclic voltammetry) and theoretical (DFT calculations) characterization of two isomeric dithieno[b,f]phosphepines (DTPs) are presented herein. The relative orientation of the phosphepine and the thiophene moieties has a decisive impact on the electronic and structural properties of these compounds. Moreover, the thiophene units allow for a facile subsequent functionalization through direct Pd-catalyzed C-H coupling, which renders DTPs highly promising building blocks for organophosphorus functional materials.
CRIS-Team WoS Importer:2020-02-11